A Conversation between Lewis "Lew" Aron (1952–2019) and Steven Kuchuck. Issue 6 (18th August 2022) - Aron, Lew; Kuchuck, Steven
ABSTRACT: What follows is an edited transcription of a filmed interview that was originally commissioned by the International Association for Relational Psychoanalysis and Psychotherapy (IARPP) for their Relational Voices Project. The video is available for viewing by IARPP members. The interview appears here by permission of IARPP. My memory for the details of how we invited Lew is foggy, and quite frankly, I didn't have the heart to go back through my e-mails with him in order to refresh my memory. I do know that I was President-elect of IARPP at the time the idea was conceived by us on the Board's Executive Committee. Past (and now once again, current) President Susi Nebbiosi had started this video archive sometime before the decision to ask Lew. Both to my chagrin and delight, Lew asked if I would be the one to interview him. Like many, I suppose, I don't like watching myself on video and while I'm very happy behind a podium, the same isn't always true in front of a camera. I think that has probably changed to some degree since Covid forced us to get used to being on Zoom and often having our teaching and lectures filmed. But back then, I was anxious about the idea and postponed hiring the camera man and setting the date. Lew didn't seem to be in a rush either. Eventually, we confessed to each other that we had both been avoiding this, each hoping to lose some weight before filming. Alas, the clock was ticking, and the winter holidays with their temptations were upon us. We finally sat down together one week after Lew's 65th birthday, in December 2017.